2016
DOI: 10.1371/journal.pone.0156013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the sFlt-1/PlGF Ratio on Clinical Decision-Making in Women with Suspected Preeclampsia

Abstract: ObjectiveTo evaluate the influence of the soluble fms-like tyrosine kinase 1/placental growth factor ratio in physicians’ decision making in pregnant women with signs and symptoms of preeclampsia in routine clinical practice.MethodsA multicenter, prospective, open, non-interventional study enrolled pregnant women presenting with preeclampsia signs and symptoms in several European perinatal care centers. Before the soluble fms-like tyrosine kinase 1/placental growth factor ratio result was known, physicians doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 25 publications
(23 reference statements)
3
46
0
7
Order By: Relevance
“…This finding is consistent with a current prospective observational study which concluded that sFlt-1: PlGF ratio of 38 or lower can be used to predict the short-term absence of preeclampsia in women in whom the syndrome is suspected clinically [21]. Saleh et al, also observed that an elevated ratio is superior to the clinical diagnosis of PE for predicting an adverse pregnancy outcome and a low ratio is inversely correlated with prolongation of pregnancy [22]. …”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with a current prospective observational study which concluded that sFlt-1: PlGF ratio of 38 or lower can be used to predict the short-term absence of preeclampsia in women in whom the syndrome is suspected clinically [21]. Saleh et al, also observed that an elevated ratio is superior to the clinical diagnosis of PE for predicting an adverse pregnancy outcome and a low ratio is inversely correlated with prolongation of pregnancy [22]. …”
Section: Discussionsupporting
confidence: 89%
“…The impact of the sFlt‐1/PlGF ratio test as an aid to diagnosis and clinical decision‐making has been investigated in Austria and Germany in the PreOS study, where the test is in routine clinical use in accordance with their local guidelines. The cut‐off ratio of 85 was considered in PreOS to confirm the diagnosis of pre‐eclampsia and inform management of women with suspected pre‐eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of the ratio between two angiogenic placental factors involved in the formation of new blood vessels – serum fms‐like tyrosine kinase‐1 (sFlt‐1) and placental growth factor (PlGF) – has provided valuable diagnostic information and forms the basis of the first automated biomarker test for pre‐eclampsia, the Elecsys® sFlt‐1/PlGF immunoassay ratio (Roche Diagnostics GmbH, Mannheim, Germany). PreOS, a multicenter, non‐interventional study evaluating the test for its aid in diagnosis and clinical decision‐making, found that changed decisions due to test results regarding hospitalization were in agreement with the maternal and neonatal outcomes. Recently, PROGNOSIS, a global, multicenter, non‐interventional study derived and validated cut‐off values for the short‐term prediction of pre‐eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Klein et al . conducted a multi‐centre, prospective non‐interventional study (PreOS) of the application of the sFlt‐1/PlGF ratio in decision‐making in women with suspected PE, The results suggested that use of angiogenic markers significantly impacts both the decision to hospitalise patients appropriately and stratifies the risk, and may help to guide the required intensity of patient management …”
Section: Prediction Of Diseasementioning
confidence: 99%